2015
DOI: 10.18869/acadpub.mlj.9.5.53
|View full text |Cite
|
Sign up to set email alerts
|

Association of the CETP TaqIB Polymorphism with Coronary Artery Disease in Type 2 Diabetic Patients

Abstract: Background and Objective: Diabetes mellitus is the most common risk factor for coronary artery disease (CAD). Cholesteryl ester transfer protein (CETP) TaqIB polymorphism is associated with changes in lipid profile and may be a risk factor for CAD in patients with diabetes. This study aimed to evaluate the association of CETP TaqIB polymorphism with CAD in patients with type 2 diabetes.Methods: In this case-control study, 292 diabetic patients were divided into two groups based on angiography reports (150 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
4
2
1
Order By: Relevance
“…Parallel with our result, other studies have reported an insignificant association between lipid profile and CETP Taq1B polymorphism. [56][57][58] By contrast to our results, some studies showed a significant association of CETP Taq1B polymorphism with HDL-C concentrations. [59][60][61] This inconsistency might relate to some factors such as sample size, ethnic group and underlying disease.…”
Section: Notecontrasting
confidence: 99%
See 4 more Smart Citations
“…Parallel with our result, other studies have reported an insignificant association between lipid profile and CETP Taq1B polymorphism. [56][57][58] By contrast to our results, some studies showed a significant association of CETP Taq1B polymorphism with HDL-C concentrations. [59][60][61] This inconsistency might relate to some factors such as sample size, ethnic group and underlying disease.…”
Section: Notecontrasting
confidence: 99%
“…According to our previous study, 25 although the HDL‐C concentrations in B2B2 patients were higher than for the B1B1 genotype, the relationship between the genotypes and HDL‐C levels was not significant. Parallel with our result, other studies have reported an insignificant association between lipid profile and CETP Taq1B polymorphism 56–58 . By contrast to our results, some studies showed a significant association of CETP Taq1B polymorphism with HDL‐C concentrations 59–61 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations